In-situ construction of Bi24O31Br10-decorated self-supported BiOBr microspheres for efficient and selective photocatalytic oxidation of aromatic alcohols to aldehydes under blue LED irradiation. Issue 3 (June 2022) - Fan, Yajun; Mo, Yuyan; Zhao, Xiaoyang; Zuo, Xiaoxi; Nan, Junmin; Xiao, Xin
Abstract: The efficient and selective oxidation of aromatic alcohols into corresponding aldehydes under mild conditions is an encouraging but challenging topic in catalysis chemistry and the chemical industry. Herein, a novel Bi24 O31 Br10 -decorated BiOBr composite was synthesized by an in-situ phase transformation route, in which BiOBr microspheres used as 3D self-supported carriers, and Bi24 O31 Br10 nanosheets are highly dispersed and anchored on the surface of BiOBr microspheres. The as-synthesized composite photocatalysts showed superior selectivity and conversion efficiency for the photocatalytic oxidation of aromatic alcohols under blue LED irradiation. The excellent catalytic performance of Bi24 O31 Br10 -decorated BiOBr is ascribed to its structural relationship between the two components and the dense heterojunction interface, which exposes more active sites and accelerate the spatial charge carriers' separation. Based on the identification of reactive species (RS) and density functional theory (DFT) calculations, a two-step oxidation mechanism of aromatic alcohols was proposed. In particular, the respective roles of the reactive species, the reason for the first hydrogen loss of aromatic alcohols, and the effects of different substituents on their selectivity were clarified at the molecular level. It is hoped that this work can provide a feasible paradigm for the spatial structure design of different components in heterojunction catalysts to improve the efficiency and selectivity of photocatalytic reactions. Graphical Abstract: ga1 Highlights: Bi24 O31 Br10 surface-decorated BiOBr microspheres was synthesized by in-situ transform route. The synthetic catalyst showed excellent oxidation activity of aromatic alcohols under blue LED. ＞99% conversion and ＞99% selectivity for BA/BAD were achieved in 30 min reaction. A two-step dehydrogenation mechanism was proposed by experimental and theoretical studies. The roles of reactive species and reason for selectivity of aromatic alcohols were elucidated.